Risk Analysis of the Prijetan Dam in Lamongan Regency - Pakpahan, Samuel Seprian; Sangkawati, Sri; Suharyanto, Suharyanto (Journal La Multiapp, 2024)
The Prijetan Dam in Lamongan, East Java, has been in operation for over a century, making it one of the oldest dams in Indonesia. This study aims to assess the risks associated with the aging structure of the dam, including potential failures and safety concerns. The analysis was conducted using the ICOLD modified risk scoring system and the Failure Mode Effects Analysis (FMEA) method, taking into account physical deterioration, climate change impacts, and possible failure modes. The results provide insights into the current physical condition, risk levels, and necessary mitigation strategies to enhance the dam's safety and functionality. The study also prioritizes maintenance and rehabilitation actions based on risk levels, ensuring long-term operational safety and security for the surrounding areas.